The quadrants of regional performance in Colombia (2000-2012) (2014)
At territorial scale economic growth has been uneven. Current trends point to a growing gap in the interregional income (or interdepartmental, in a strict sense), whose overcoming cannot be left to the automation market. In Latin America the persistence of interregional disparities is in the research agenda of ILPES and ECLAC since the past decade, because it affects the possibilities of regional development. In Colombia, concern about regional inequalities in the regional analysis, dates back to the nineties, and was focused on the identification of converging or diverging trends, whose results were inconclusive. The analysis of the economic performance of the Colombian departments and Bogota, during the period 2000 2012, using the technique of the quadrants, proposed by ILPESECLAC, has revealed that the winners territories (quadrant 1) have decreased, while the largest number has concentrated, in constant movement, in quadrants 2 and 3, that is, in the converging and stagnant areas while declining territories do not show substantial change. Interregional disparities do not appear to be attenuated, on the contrary, are accentuated. The interregional gap persists and structural change of departmental economies has deepened  it.